Apoptotic and nonapoptotic function of caspase 7 in spermatogenesis - Lei, Bin (Asian J Androl, 2017)
Recent studies have reported that caspase 7 has an apoptotic and nonapoptotic function. However, the relationship between caspase 7 and spermatogenesis remains unknown. This study aimed to investigate the possible function of caspase 7 during normal and abnormal spermatogenesis. The cleaved form of caspase 7 was detected in testis tissues at different postpartum times (5–14 weeks) by qRT-PCR, Western blot and immunohistochemistry (IHC). Then, the mice models of spermatogenic dysfunction were obtained by busulfan (30 mg kg(−1) to further evaluate the potential function and mechanism of caspase 7. qRT-PCR and Western blot results showed that caspase 7 expression was gradually elevated from 5 to 14 weeks, which was not connected with apoptosis. IHC results revealed that caspase 7 was mainly located in spermatogenic cells and Leydig cells. In addition, spermatogenic dysfunction induced by busulfan gradually enhanced the apoptosis and elevated the expression of caspase 3, caspase 6, and caspase 9, but decreased the expression of caspase 7 in spermatogenic cells. However, when spermatogenic cells were mostly disappeared at the fourth week after busulfan treatment, caspase 7 expression in Leydig cells was significantly increased and positively correlated with the expression of caspase 3, caspase 6, and caspase 9. Therefore, these results indicate that caspase 7 has a nonapoptic function that participates in normal spermatogenesis, but also displays apoptotic function in spermatogenic dysfunction.